Gene expression in obstetric antiphospholipid syndrome: a systematic review - Muhammad Aliff, M; Muhammad Shazwan, S; Hayati, AR; Jameela, S; Prof. Madya Dr. Asral Wirda Binti Ahmad Asnawi; Nur Fariha Mohd Manzor; Nur Syahrina Rahim; Maizatul Azma Masri; Nazefah Abdul Hamid (Malaysian Journal Pathology, 2024)
Indexed by WOS